Food purchasing pattern is correlated to gender, educational level, and income: Results from the food purchasing habits survey - Hiba F. Al-Sayyed; Zeinah F. AbuZeinah; Narmeen J. Al-Awwad (PLoS ONE, 2025)
Food purchasing pattern refers to the consumer behavior related to buying food. Rice and bread are the staple foods of Jordan. Legumes, cereals, milk, and dairy products constitute important part of the Jordanian diet. This cross-sectional study aimed to investigate food shopping patterns of people living in Jordan for milk, dairy products (e.g., yogurt, cheese), legumes and grains (rice, bulgur, freekeh, and couscous), and cereals (such as breakfast cereals, oatmeal, and granola). The study also aimed to understand the importance of certain consumer-related factors (like sociodemographic characteristics), product-specific factors (like taste, packaging, and origin (local vs. imported)), and external factors (like cost, brand name, freshness, and production/expiry dates) on the purchasing of these products. Most of the study participants were adult (18–30, n = 64.4%), educated (48.6%) females (75.6%). Female gender was correlated significantly (P < 0.05*) to purchasing local milk, dairy products and cereals due to freshness and famous brand names. In addition, socioeconomic status (indicated by household income and education level) affected significantly (P < 0.05) the type of milk and cereals purchased where price, freshness, participants’ perception of packaging and ingredient list, expiry date, and brand name affected purchasing of cereals and milk. Furthermore, age was found to be a significant (P < 0.05) determinant to buying local cereal products. Results of this investigation could be utilized by manufacturers and policy makers to improve the nutritional quality of food products offered in the Jordanian market, advertise for better local food choices, and to adopt focused strategies in order to develop the food sector in Jordan. Consumer behavior is a fundamental part of human daily lives. Studying consumer behavior pertains analyzing the factors affecting and affected buying goods.